Characterisation of Amaranthus Tricolor mutant plants with increased drought-tolerance - Kgang, Itumeleng Eugenia (Vaal University of Technology, 2010)
Amaranthus tricolor (A. tricolor) is a nutritious vegetable crop that is used as a subsistence and cash crop in the rural areas in Africa. Its yield and production is severely limited by abiotic stresses such as drought. Mutation technology, using gamma irradiation, was previously employed as a tool to create genetic variation in order to select for lines with improved drought-tolerance. During irradiation, 160 Gy (Gray) was selected as the optimal dosimetry that allowed subsequent seed germination. The resulting mutant lines were screened over several generations under field and greenhouse conditions and seven promising drought-tolerant lines were selected. Here we report on physiological and morphological studies of two of these Amaranthus mutant lines (#2 and #5) to confirm the enganced drought-tolerance. Plants were grown in the greenhouse in plastic pots containing germination mix with fertiliser. They were exposed to 21 days of well-watered condition, 19 days of drought-stress conditions and 7 days of re-watering. shoot height, leaf area, protein content and relative water content (RWC) of the fresh and dry material were determined colorimetrically under well-watered and drought-stress conditions, while anthocyanin was only measured during well-watered conditions. Shoot height, leaf area, number of leaves per plant and the protein content were significantly reduced under water-stress conditions. Under well-watered condition mutant #5 grew faster with the shoot length significantly higher than mutant #2 and the wild type. Even though drought adversely affected shoot lenght, mutant#5 still performed better than mutant #2 and the wild type under drought-stress conditions. While under both well-watered and drought-stress conditions, the wild type plants had bigger leaf area compared to the two mutant lines. After 16 days of drought-stress conditions, all the leaves of the wild type plants were dried out, as a result no wild type plants recovered after 8 days re-watering. Meanwhile, both mutant #2 and #5 plants recovered significantly after 8 days of re-watering. The wild type was tolerant compared to the two mutant lines. Protein content for mutant #2 plants was higher under both well-watered and drought-stress conditions but was not significantly different from mutant #5 plants compared to the wild type plants after 19 days of drought-stress conditions. Furthermore, genetic diversity was examined in all the Amaranthus lines using random amplified polymorphic DNA (RAPD) analysis. Nineteen arbitrary RAPD markers were used of which two detected polymorphisms (OPA) 07 and OPA 16).
M. Tech. (Biotechnology, Department of Health Sciences, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Amaranthus tricolor; Gamma irradiation; Genetic variations; Drought-tolerance; 581.754; Drought resistant plants.; Genetically modified crops.; Amaranth greens.